A general strong law of large numbers for non-additive probabilities and its applications. Issue 4 (3rd July 2016) - Hu, Feng; Chen, Zengjing; Wu, Panyu
Abstract : In this paper, with the notion of independence for random variables under upper expectations, we derive a strong law of large numbers for non-additive probabilities. This result can be seen an extension version of Theorem 3.1 that Chen et al. [A strong law of large numbers for non-additive probabilities. Int J Approx Reason. 2013;54:365–377] yielded. Furthermore, two applications of our result are given.